Qalbun Salim Menurut Ahmad Musthafa Al-Maraghi - Siregar, Rahmadani; Enghariano, Desri Ari (Jurnal El-Thawalib, 2022)
Al-Qur’an is the word of Allah swt which sometimes has words in it that hold many meanings like the word qalbun salim. The word qalbun salim which is implied in the qur’an by mufassir which has many meanings, one of which is a clean heart and a safe heart. One of the commentators, Ahmad Musthafa Al-Maraghi, said that the heart of qalbun salim is a clean heart and a safe heart.As for the formulation of the problem of this research, how is the interpretation of the verses about qalbun salim according to Ahmad Musthafa Al-Maraghi. The purpose of this study is to find out the interpretation of the verses about qalbun salim according to Ahmad Musthafa Al-Maraghi.As for this research is library research, namely library research, which collects data sources in the form of primary and secondary library materials. The primary data source in this study is al-Maraghi’s interpretation and the secondary data sources in this study are books, journals, and books related to this research. The interpretation of verses about the heart of qalbun salim is the keyword of the qur’an in the thematic method, by collecting data on all verses related to the topic of qalbun salim.From the previous explanation the author concluded that Ahmad Musthafa Al-Maraghi said the word qalbun salim in the Qur’an, namely qalbun salimis the heart that is safe from shirk and empties his heart from actions that pollute his heart in the form of false beliefs and bad traits. Thean his heart becomes clean from sin and immorality and abstains from acts that are forbidden by Allah swt. Because on the day of resurrection a person cannot be protected  from the punishment of Allah with wealth, even if he redeems it with gold all the earth and not with the son he has.